A framework for managing virtual objects in virtual environment - Wan Mohd Rizhan Wan Idris (Fakulti Sains dan Teknologi, 2012)
Nowadays, many applications have been utilizing the virtual reality in their tasks and works such as in architecture, medicine, advertisement, business, entertainment, and education. Virtual reality refers to the use of computers and other devices; and software to generate the world of simulation. Through the virtual reality, users are able to visualize, manipulate and interact with the computers and complex data to generate another world.